Investigation on the Properties of HPC Exposed to Elevated Temperatures - Aidoud, Assia; Benouis, Abdelhalim (Asian Journal of Engineering and Applied Technology, 2016)
When concrete is subjected to elevated temperatures, a destruction of its constituent hydration products can be occurred. This destruction implies a weakening of the material degradation of its mechanical properties such as stiffness and strength. The elevated temperature generates significant fluid pressure, leading to damage it and also causing breakdown of the concrete, which is characterized by the deteriorations of the hydrated material.This study focuses the evolution of residual properties of three High performance concrete (HPC). The specimens (16×32) cm2 were subjected to different temperatures: 200°C, 400°C and 600°C with a rate of 2°C/min followed by a stage of three hours at the target temperature and then cooling to room temperature. The evaluation of different properties was evident compared to room temperature (20°C), with a maximum drop of compressive strength is of 79%. The loss of tensile strength is 62%. Losses masses and decreases dynamic elastic modulus are 6% and 89% respectively. It was observed an explosive burst of one of HPC between 400°C and 600°C.